Analysis of College Students’ Physical Health Test Data Based on Big Data and Health Promotion Countermeasures - Ming Li; Fengcai Wang (Advances in Multimedia)
In order to improve the data analysis and health promotion effect of college students' physical health test, this paper combines the big data technology to carry out the analysis and health promotion system of college students’ physical health test data. Moreover, this paper analyzes and discusses the overall control strategy of the high-precision time-base calibrator and the time-base phase-locked synchronization method and studies the overall scheme design and system working process of the precision time-base calibrator in combination with the requirements of physical health testing. In addition, this paper conducts mathematical derivation and theoretical simulation analysis on the A/D conversion accuracy, noise source and influence, time-frequency characteristics, and corresponding speed of the second-order generalized integrator and constructs an analysis and health promotion system of college students’ physical health test data. The research results show that the college students’ physical health test data analysis system proposed in this paper has certain reliability, and on this basis, college students' health promotion countermeasures are proposed.